Structural Equation Modelling (SEM) on Teacher Competencies Test of Indonesian EFL Senior High School Teachers - Dwi Rahmani, Bita; Alyani, Fitri (LPPM Undiksha, 2020)
The purpose of this paper is to investigate what factors influenced on Teacher competencies Test (Uji Kompetensi Guru/UKG) of Indonesian ESL Senior High School teacher’s in West Java Indonesia. The data used in this study were derived from a teacher competencies test, and a questionnaire survey conducted among teachers who attended National Gathering of Senior High School English Teachers 2017 in Bandung, West Java. A total of 61 usable responses were received. The analysis was using Structural Equation Model (SEM) to see the correlations among variables also identify which predictors influenced most on Teacher Competencies Test. The result revealed that teacher competencies test was mostly influenced by education background (β =.27, p=0.028). It can be concluded that to increase the teacher’s competencies can be done by giving a chance to teachers to continue their study.